Integration of Hybrid and Single Ventricle Rehabilitation Techniques to Treat a Neonate After Iatrogenic Mitral Injury. (July 2016) - Ashfaq, Awais; Seckeler, Michael; Pophal, Stephen; Rhee, Edward; Ryan, Justin; Rao, Rohit; Klewer, Scott; Nigro, John J.
Neonatal critical aortic stenosis is life threatening and requires intervention shortly after birth. Early percutaneous aortic valvuloplasty is generally considered to be an effective way to obtain reliable prograde flow. We describe the integrated use of hybrid, open surgical, and single ventricle rehabilitation techniques to successfully treat a neonate with borderline left-sided cardiac structures, who sustained a complication from balloon aortic valvuloplasty.